2010
DOI: 10.1183/09031936.00028010
|View full text |Cite
|
Sign up to set email alerts
|

Association of airflow limitation with trauma exposure and post-traumatic stress disorder

Abstract: Trauma exposure and post-traumatic stress disorder (PTSD) are associated with self-reported asthma and chronic obstructive pulmonary disease. However, these conditions have not yet been related to objective measures of lung function.1,772 adults from the general population were assessed regarding their medical histories and spirometric lung function. Additionally, they were administered a PTSD interview, and assigned to three groups: no trauma; trauma, but no PTSD; and trauma with PTSD.Adjusting for sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 54 publications
2
28
0
3
Order By: Relevance
“…However, a significant inverse association was shown between (12 months and lifetime) major depression and FEV1 and forced expiratory flow at 25-75% of FVC, but only in males. These studies, in addition to the study by SPITZER et al [33], suggest some evidence of associations with lung function but the results are inconsistent. Therefore, it remains uncertain whether the respiratory symptoms associated with psychosocial factors are due to airway obstruction or other factors not directly related to asthma (or other respiratory conditions such as COPD).…”
Section: Table 1 Continuedmentioning
confidence: 85%
See 1 more Smart Citation
“…However, a significant inverse association was shown between (12 months and lifetime) major depression and FEV1 and forced expiratory flow at 25-75% of FVC, but only in males. These studies, in addition to the study by SPITZER et al [33], suggest some evidence of associations with lung function but the results are inconsistent. Therefore, it remains uncertain whether the respiratory symptoms associated with psychosocial factors are due to airway obstruction or other factors not directly related to asthma (or other respiratory conditions such as COPD).…”
Section: Table 1 Continuedmentioning
confidence: 85%
“…Studies involving objective measures of respiratory health effects, such as the one by SPITZER et al [33] published in this issue of the European Respiratory Journal, may shed some light on these issues. The authors conducted cross-sectional analyses (nested within a cohort study) of the associations between lung function, as an objective measure of airway obstruction, and trauma exposure and PTSD in 1,772 adults from the general population.…”
mentioning
confidence: 99%
“…28 Another study found a strong relationship between PTSD and asthma symptoms, and also reported a relationship between traumatic stress and pulmonary function. 29 For these reasons, we plan additional studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, results from a concurrent genetic association study and experiments in murine models further implicated alterations in the PACAP-PAC1 receptor pathway in the causality of PTSD. Given those novel findings, a reported link between PTSD and asthma morbidity (13), and our previous findings in Puerto Rican children, we hypothesized that DNA methylation or genetic variation in ADCYAP1R1 would be associated with childhood asthma in Puerto Ricans. We examined this hypothesis in a case-control study of asthma in children living in San Juan, Puerto Rico.…”
mentioning
confidence: 99%